GAME EDUKASI PENGEMBANGAN GAME EDUKASI I’TIKAD 50 BERBASIS POWER POINT DI DAYAH AL-FURQAN ACEH BESAR - Bustami Yusuf; Intan Maulina; Mulkan Fadhli (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study is to answer the problem of developing power point-based i'tikaf 50 educational games in Dayah Al-furqan Aceh Besar because students are not very interested in lecture or conventional learning systems. Therefore, an educative and interesting game was made in learning I'tiqad 50. The method used in the research was R&D (Research and Development) or research development. The results of the validation test by the validator were 16 respondents with the aspect of material assessment getting a score. as much as 77.2%, and the media assessment aspect got a score of 78.2%. The results of the implementation of the I'tikad 50 educational game learning media which were applied to the control class (KK) in Dayah Al-furan obtained an average score of 89.3 and the traditional (conventional) learning outcomes were applied to the ordinary class (KB) in Dayah Al -furqan obtained an average score of 74.6.